2011
DOI: 10.1007/s12010-011-9352-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Stability and Instability of Tissue Culture-Propagated Plantlets of Aloe vera L. by RAPD and ISSR Markers

Abstract: Efficient plantlet regeneration with and without intermediate callus phase was achieved for a selected genotype of Aloe vera L. which is sweet in test and used as a vegetable and source of food. Random amplified polymorphic DNA (RAPD) and inter simple sequence repeats (ISSR) marker assays were employed to evaluate genetic stability of plantlets and validate the most reliable method for true-to-type propagation of sweet aloe, among two regeneration systems developed so far. Despite phenotypic similarities in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 27 publications
6
28
0
4
Order By: Relevance
“…The results of this molecular study revealed that all the primers used in this study showed a monomorphic pattern in all the sample plants, confirming the genetic uniformity of the regenerated plantlets and that no variation was induced during in vitro propagation of A. marina (Figures 3À5). The findings of this investigation corroborate several earlier reports on genetic analysis of regenerated plantlets in Mentha arvensis, [16] Aegle marmelos, [27] Bambusa balcooa, [28] Gerbera jamesonii [29] and Gloriosa superba [30], using SPAR analysis.…”
Section: Genetic Fidelity Of Regenerated Plantssupporting
confidence: 91%
“…The results of this molecular study revealed that all the primers used in this study showed a monomorphic pattern in all the sample plants, confirming the genetic uniformity of the regenerated plantlets and that no variation was induced during in vitro propagation of A. marina (Figures 3À5). The findings of this investigation corroborate several earlier reports on genetic analysis of regenerated plantlets in Mentha arvensis, [16] Aegle marmelos, [27] Bambusa balcooa, [28] Gerbera jamesonii [29] and Gloriosa superba [30], using SPAR analysis.…”
Section: Genetic Fidelity Of Regenerated Plantssupporting
confidence: 91%
“…Por ende, al igual que la propagación, es de importancia mantener la integridad genética derivada de las plantas propagadas bajo estas condiciones. La variación somaclonal puede originarse bajo ciertas situaciones de estrés que se producen durante el cultivo in vitro, los factores que la originan son diversos y han sido estudiados en algunas especies (Tabla 1) (Sharma et al, 2007Chandrika et al, 2010Rathore et al, 2011;Regalado et al, 2015).…”
Section: Datos No Publicados)unclassified
“…Para realizar la reintroducción de individuos que han sido obtenidos por propagación masiva in vitro, a su hábitat natural uno de los requisitos es que se desarrolle un eficiente sistema de multiplicación de individuos élite con alta fidelidad genética (Rathore et al, 2011 En este estudio se aplicaron marcadores ISSR para analizar la estabilidad genética de 84…”
Section: Variación Somaclonalunclassified
See 1 more Smart Citation
“…Generation of micropropagated plants of A. vera through in vitro culture and their field transfer has been reported by many workers (Wenping et al 2004, Liao 2004, Aggarwal and Barna 2004, Rathore et al 2011, but very few of them have studied the long term evaluation of field grown micropropagated plants in this species, even though it is essential for commercial production. Tissue culture induces variation which can result in a range of genetically stable variation, useful in crop improvement (Larkin and Scowcroft 1981).…”
Section: Introductionmentioning
confidence: 99%